Quality of life in patients with slowly progressive neuromuscular disorders dependent on mechanical ventilation. Issue 1 (1st September 2022) - Delorme, Mathieu; Reveillere, Christian; Devaux, Christian; Segovia-Kueny, Sandrine; Lofaso, Frédéric; Boussaid, Ghilas
Abstract : This cross-sectional study evaluated health-related quality of life (HRQoL) in patients with slowly progressive neuromuscular disorders dependent on mechanical ventilation (MV; ≥16 hours/day). 119 participants, with 9 years (25th–75th percentiles: 4–15 years) of MV dependence, were included. MV was applied via a tracheostomy in 80 participants (67.2%) and non-invasive interfaces in 39 participants (32.8%), including 28 participants (71.8%) with daytime mouthpiece ventilation. HRQoL was rated good or excellent by 81 participants (68.1%), independently from age, diagnosis or respiratory autonomy. On multivariate analysis, time since MV initiation, independence from family member(s), residence in a rural area, ability to go outdoors with MV and tracheostomy were associated with better HRQoL.